Clinical practice of traditional Chinese medicine for the treatment of postmenopausal osteoporosis: a literature review. (2nd November 2022) - Li, J.; Fu, S.-F.; Yang, Y.; An, R.; Liu, H.-Y.; Mao, H.-P.
Abstract: Objective: This study aimed to evaluate the effectiveness and safety of traditional Chinese medicine (TCM) for postmenopausal osteoporosis (PMOP). Methods: We conducted a computer literature search in five databases and comprehensively extracted all kinds of information from each article. Traditional Chinese medicine inheritance support system (TCMISS) V2.5 was adopted to perform association analysis. The effectiveness, safety and methodological quality were analyzed using randomized controlled clinical trials (RCTs). Results: A total of 2880 related articles were collected. Finally, 423 articles which included 312 RCTs were included for in-depth analysis. We collected 369 Chinese medicine prescriptions and found that the top three frequently used herbs in the treatment of PMOP were Epimedii Folium (Yinyanghuo), Rehmanniae Radix Praeparata (Shudihuang) and Angelicae Sinensis Radix (Danggui). The top Chinese patent medicine was Gushukang capsule. No serious adverse reaction (AR) had been reported in the Chinese medical treatment group. Conclusion: The effectiveness of TCM in treating PMOP needs to be further explored, and the safety is good. Therefore, high-quality evidence is urgently needed to supplement.